The Role of Emotional Intelligence in Effective Decision-Making - Nur Khalisah (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
The purpose of this research was to analyze how EQ relates to managerial performance in Malaysia. One hundred fifty managers were polled on their EQ, personality type, and effectiveness on the work. Emotional IQ was found to have a favorable relationship with both rational and intuitive decision-making styles (r =.43, p .001), but a negative relationship with rational decision-making style (r = -.24, p .05). After accounting for factors such as age, gender, level of education, and length of employment, emotional intelligence was still found to be a significant predictor of work success (r=.33, p .001). The results of this study have significant consequences for Malaysian businesses and their leaders. The findings imply that administrators can benefit from enhanced decision-making and productivity by boosting their emotional intelligence. Better organizational outcomes, like improved productivity and profits, may result from this. But the present research has some restrictions, like using self-report measures and only surveying managers in Malaysia for its sample. A more diverse sample of individuals from a variety of settings, as well as more objective measures of emotional intelligence and decision-making, could improve future studies. This research contributes to the expanding literature on the importance of EQ to success in life and the workplace. The results indicate that emotional intelligence is a valuable trait for managers to have, and that businesses would do well to encourage their employees to cultivate these abilities.